2020
DOI: 10.3390/pathogens9090697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pathology, Immunopathology and Advanced Vaccine Technology in Bovine Theileriosis: A Review

Abstract: Theileriosis is a blood piroplasmic disease that adversely affects the livestock industry, especially in tropical and sub-tropical countries. It is caused by haemoprotozoan of the Theileria genus, transmitted by hard ticks and which possesses a complex life cycle. The clinical course of the disease ranges from benign to lethal, but subclinical infections can occur depending on the infecting Theileria species. The main clinical and clinicopathological manifestations of acute disease include fever, lymphadenopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 167 publications
(227 reference statements)
1
26
0
Order By: Relevance
“…Inflammatory cytokines play a major role during the process of liver inflammation, especially from steatosis to steatohepatitis, or from inflammatory infiltration to liver injury [31]. Previous studies reported that carbohydrates, therapeutic drugs and the hypoxia/reoxygenation model could increase the levels of IL-1 β and IL-6 in the supernatant of BRL-3A cells [13,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines play a major role during the process of liver inflammation, especially from steatosis to steatohepatitis, or from inflammatory infiltration to liver injury [31]. Previous studies reported that carbohydrates, therapeutic drugs and the hypoxia/reoxygenation model could increase the levels of IL-1 β and IL-6 in the supernatant of BRL-3A cells [13,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…During a tick bite, infective sporozoites are transmitted to the cattle host. Clinical disease caused by T. annulata and T. parva occurs when sporozoites infect leukocytes and develop into macroschizonts, which induces uncontrolled leukocyte proliferation [19]. By contrast, it is the T. orientalis piroplasm stage, which infects the host red blood cells, causing anemia that is ultimately associated with the clinical signs of acute oriental theileriosis [20].…”
Section: Vaccines Against Theileria Spp Of Importance To Cattlementioning
confidence: 99%
“…However, MPSP is highly diverse, which may affect its wide use as a vaccine antigen. In addition, considering the MPSP diversity, this target has been used to classify T. orientalis into several distinct genotypes worldwide [19,75,76]. Recent studies on the T. orientalis draft genome have revealed interesting features among the Ikeda, Chitose, and Buffeli genotypes that can be explored for vaccine development.…”
Section: Vaccines Against Theileria Spp Of Importance To Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…Diarrhea, anorexia, high fever, thinness, lethargy, swelling of the lymph nodes, eyelid swelling, increased pulse and panting, profuse lachrymation, anaemia, icterus, and death are all symptoms of theileriosis(AginaShaari et al 2020). Unfortunately, the mechanism of the pathogenesis of malignant ovine theileriosis is not well known yet (Agina et al 2020). Identi cation of Theileria spp.…”
Section: Introductionmentioning
confidence: 99%